Parental psychopathology and offspring anxiety disorders in childhood and adolescence: A Finnish nationwide register study - Khanal, Prakash; Ståhlberg, Tiia; Upadhyaya, Subina; Heinonen, Emmi; Ortin-Peralta, Ana; Sourander, Andre (Elsevier, 2025)
Background
Research suggests an association between parental psychiatric disorders and offspring anxiety disorders, yet comprehensive studies are limited. This study aims to investigate the associations between various parental psychiatric disorders and anxiety disorders in their offspring.
Method
Using Finnish register data, this nested case-control study analyzed 867,175 singleton live births from 1992 to 2006, identifying 21,671 cases of anxiety disorders diagnosed between 1998 and 2016. Matched with four controls each (n = 72,414) based on age and biological sex, the study adjusted for demographic and prenatal factors using conditional logistic regression models to calculate odds ratios (aORs).
Results
There was a significant association between parental psychiatric disorders and increased risk of anxiety disorders in offspring. The risk was notably higher when both parents had psychiatric disorders (aOR = 5.04; 95 % CI, 4.70‐5.39; p < .001). Maternal psychiatric disorders were strongly associated with offspring anxiety than paternal disorders (aOR 1.52; 95 % CI 1.43–1.61; p < .001). This association was consistent regardless of timing of parental diagnosis. Significant associations were observed between any parental psychiatric disorder and increased risks in offspring for specific phobia, social phobia, generalized anxiety disorder, separation anxiety, and panic disorder. Maternal psychiatric disorders showed elevated risk for panic disorder and social phobia among girls and separation anxiety and generalized anxiety among boys.
Conclusion
The findings emphasize the significant impact of parental psychiatric health on offspring anxiety disorders, highlighting the influence of genetic and environmental factors. Addressing parental mental health is crucial in preventing childhood anxiety disorders.